Intraoperative aberrometry-assisted refractive optimization of SFIOL - Saurabh Verma; Pradeep Venkatesh; Shorya Vardhan Azad; Devesh Kumawat; Sudarshan Khokhar (Indian Journal of Ophthalmology)
Scleral-fixated intraocular lens (SFIOL) is a widely used technique for IOL implantation in patients where capsular support is insufficient. Most surgeons have shifted away from sutured to sutureless SFIOL techniques where haptics of a multifocal IOL are inserted in scleral tunnels/flaps. Large-scale publications have shown wide variation in the refractive status of eyes post-SFIOL even in the best of the hands. This is because even slight variations in the site of scleral flap/tunnel formation and tension on haptics due to the variable length of haptics placed in scleral flaps/tunnels can alter the effective lens position and induce significant residual refractive error, especially cylindrical astigmatism due to IOL tilt. Our technique aims to reduce residual refractive error after SFIOL implantation. This is achieved by using intraoperative aberrometry and adjusting haptics accordingly to achieve minimal refractive error intraoperatively.